2022
DOI: 10.1093/jxb/erac443
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones in plant responses to boron deficiency and toxicity

Abstract: Summary Boron (B) is an essential element for plant growth. Many agricultural soils around the globe have either insufficient or excessive amounts of available B, with major implications for crop production. Understanding major limitations imposed by B nutritional disorders may allow breeding crops for improved B use efficiency as well as make them more resilient to excessive B, thus reducing yield penalties. It has become apparent that B-related physiological disorders are mediated in large par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…Jasmonic acid is a positive regulator of immunity against necrotrophic pathogens and herbivory (Berens et al, 2017). It has also recently been implicated in negatively regulating growth in response to B‐deficiency in A. thaliana seedlings (Huang et al, 2021a,b) and increased jasmonic acid biosynthesis under B‐limitation has been reported in B. napus (Zhou et al, 2016) and other species (Chen et al, 2022). WRKY transcription factors have also been shown to play diverse roles in plant defence, involved in both detection and the response to pathogens and other biotic stresses (Sarris et al, 2015; Jiang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Jasmonic acid is a positive regulator of immunity against necrotrophic pathogens and herbivory (Berens et al, 2017). It has also recently been implicated in negatively regulating growth in response to B‐deficiency in A. thaliana seedlings (Huang et al, 2021a,b) and increased jasmonic acid biosynthesis under B‐limitation has been reported in B. napus (Zhou et al, 2016) and other species (Chen et al, 2022). WRKY transcription factors have also been shown to play diverse roles in plant defence, involved in both detection and the response to pathogens and other biotic stresses (Sarris et al, 2015; Jiang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the same structural defects were recently identified also in boron uptake mutant (Panter et al ., 2023) which implies a link between uptake of boron and morphology of OCLs. However, it cannot be excluded that the cuticle composition changes are a secondary effect of stress signaling (Voxeur et al ., 2017; Chen et al ., 2022). The precise function of OCLs is still poorly characterized (Hunt & Gray, 2020); however, changes in OCL structure provide little explanation for additive water loss observed in double mutants of mur1 and guard cell signaling components (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When reaching this zone, the local increase in auxin concentration, in combination with ROS accumulation, inhibits root elongation (Martín‐Rejano et al ., 2011; K. Li et al ., 2015). Furthermore, auxin stimulates the synthesis of ethylene (ET) precursors, which is a stress hormone that further promotes ROS accumulation, inhibits cell elongation in the root tips, and induces root hair formation (Martín‐Rejano et al ., 2011; Chen et al ., 2023b).…”
Section: Boronmentioning
confidence: 99%